THE EFFECT OF HYDROPONIC NUTRITION LEVELS ON THE GROWTH OF MUSTARD (BRASSICA SP.) PLANTS - Tience E. Pakpahan; Arie Hapsani HB; Mahmudah Mahmudah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The main roles of plant growth was nutrition. This research aims to determine the concentration of nutrients that can provide the best growth and yield on various mustard. The research method used is a factorial Complete Randomized Design (RBD) with three replications and then analyzed using the Least Significant Difference test (LSD) at a level of 5%. The treatment of vegetable types is as follows: S1 = mustard pakchoy, S2 = mustard samhong, S3 = mustard pagoda, S4 = mustard pakchoy mini. Treatment with nutrition is the AB mix fertilizerzs number of leaves solution as follows: N1 = 1000 ppm, N2 = 1200 ppm, N3 = 1400 ppm, N4 = 1600 ppm, N5 = 1800 ppm. The results showed that plant height, number of leaves, leaf width and wet weight of the pagoda and mini pakchoy plants were not significantly different at 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm and 1800 ppm. Number of leaves of pakchoy significantly different at 1400 ppm. While the number of leaves and leaf width of samhong plants were not significantly different at each treatment, but were significantly different from plant height at 1600 ppm and significantly different from the wet weight at 1400 ppm